FRACTAL CHARACTERISTICS OF DENSE STREAM NETWORKS - Schuller D.J.; Rao A.R.; Jeong G.D. (My University, 2001)
In the past, a great deal of research has been conducted to determine the fractal properties which quantify the sinuosity of individual streams and the branching configuration of stream channel networks in watersheds. Much of this work has been conducted with sparse rather than dense stream networks. It seems appropriate that characteristics should be determined for dense networks to decide if the ranges of values of the fractal characteristics computed by previous researchers hold for the dense networks. The first objective of the present study is to compute the fractal measures for several watersheds, which have dense network data, and to compare them to the values in the literature estimated by using sparse network data. The second objective is to compare the different fractal measures for different watersheds and examine their variability. If there is considerable variability in these measures, then the question of which measures to use arises. The third objective is to examine whether these watersheds are self-similar or self-affine. The results indicate that the fractal dimensions vary widely, depending on the definitions used. The watersheds have self-affine rather than self-similar characteristics.
Keywords: EUCLIDEAN; FRACTAL DIMENSIONS; WATERSHEDS